Analisis Kompetensi Pedagogik Guru Pada Proses Pembelajaran - Manik, Elawati; Nasution, Sahkolid; Sumanti, Solihah Titin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This article aims to find out how the teacher's pedagogical competence is in the learning process of Islamic religious education at the Muhammadiyah 09 Private Vocational High School in Medan. This type of research is qualitative research, with data sources taken through primary data sources, namely from the Principal, PAI Teachers, and Students, and secondary sources, namely obtained from documents and photographs related to Muhammadiyah Private Vocational School 09 Medan. Researchers act as participants. The data collection procedures through observation, interviews, and documentation. And using data analysis in the form of data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) The pedagogic competence of PAI teachers in the learning process is that teachers are able to (a) make lesson plans (RPP) well, (b), teachers are able to carry out learning properly and correctly, (c) teachers are able to provide assessments on student learning processes and outcomes, and (d) teachers are able to supervise learning optimally. 2) The PAI learning process, namely (a) the ability to understand students, (b) the ability to make learning designs, (c) Develop curriculum (d) the ability to carry out educational and dialogic learning, and (e) the ability to implement evaluation of learning outcomes. 3). The obstacles of PAI teachers in the learning process are: the number of teachers and students is not directly proportional, the result is an impact on the physical and psychological, namely fatigue when teaching children in busy hours. lack of supporting facilities and infrastructure provided by schools in the success of learning, environmental influences, and the less optimal role of parents in educating children at home.